Efficacy and cost-effectiveness analysis of flexible ureteroscopic lithotripsy with TFDS in the treatment of urolithiasis - Gao, Xiang; Han, Peng; Zong, Yiping; Wang, Zijie; Zhang, Wei; Lu, Pei (Frontiers in Surgery, 2024)
BackgroundAt present, there is no effective drug to remove residual stones. Total flavonoids of desmodium styracifolium (TFDS) is an innovative traditional Chinese medicine listed in 2022, which can be used to treat ureteral calculi. This study was to explore the effectiveness and economic value of TFDS in the treatment of residual stones after flexible ureteroscopic lithotripsy (FURL).MethodsA total of 161 patients who underwent unilateral ureteroscopic lithotripsy for urinary calculi by the same surgeon in our center from May 2022 to February 2024 were retrospectively included. According to the use of stone-removal drugs after operation, patients were divided into TFDS group and Control group. The residual stones showed by x-ray plain film when the double J tube was removed were compared between the two groups, and the economic benefits of TFDS were analyzed by cost-benefit analysis.ResultsThe data of 161 patients were collected, including 80 cases in TFDS group and 81 cases in Control group. The SFR rates at the endpoint of follow-up in TFDS group and Control group were 98.75% and 88.88%, respectively. In the subgroup analysis of post-operative residual stones, the stone clearance rate of TFDS was higher (47.62% vs. 18.18%). No obvious adverse events were reported in two groups. The cost/benefit ratio of TFDS was lower (20.43 vs. 32.57). Cost of TFDS was increased by ¥12.97 for each additional unit of total effective rate.ConclusionThe combination of dusting FURL and TFDS can effectively remove the urolithiasis when compared to only FURL, which showed highly economic benefits.